Winning the Stream War: An Empirical Comparison of Netflix and Disney+ Hotstar in the Indonesian Market - Sanjaya Budi Santoso; Prida Ariani Ambar Astuti (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The advancement of digital technology has transformed consumer behavior in accessing entertainment, with subscription video-on-demand (SVOD) services emerging as a dominant choice. This study compares Indonesian consumers’ perceptions of two leading SVOD platforms, Netflix and Disney+ Hotstar, across five key variables: user experience, subscription price, intention to subscribe, customer satisfaction, and customer loyalty. A quantitative approach was employed using purposive sampling, involving 180 respondents who had subscribed to both services within the past 12 months. Data were analyzed using SPSS and the non-parametric Wilcoxon Signed-Rank Test. Results reveal significant differences across all variables, with Netflix scoring higher than Disney+ Hotstar in each. These findings indicate that Netflix outperforms Disney+ Hotstar in delivering superior user experience, value for price, subscription intention, customer satisfaction, and loyalty among Indonesian consumers. This aligns with consumer behavior and marketing theories highlighting the influence of experience, pricing, and motivation on satisfaction and loyalty